Salib Yesus – Penderitaan Maria Devosi Maria dalam Ibadat Jalan Salib Versi Solor-Lamaholot - Paul Budi Kleden (Institut Filsafat dan Teknologi Kreatif Ledalero, 2011)
Devotion to Mary is one of the most popular religious practices among Catholics, and can be considered one of the oldest forms of popular religiosity. Marian devotions emerged spontaneously as a mixture of elements from local cultures and the Christian faith. However, such practices can become problematic when they overstress certain aspects of human experience together with the role of Mary. This article discusses a text of